The Role of Islamic Education Teachers (PAI) in Shaping the Religious Character of Students through Friday Prayers - Wahyurani, Wahyurani; Zain, Biqi (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study examines the contribution of Islamic Education (PAI) teachers in shaping students’ spiritual character through the implementation of congregational Friday prayers at SMK Negeri 3 Pacitan. The objective of this research is to describe the roles carried out by PAI teachers and to identify the supporting and inhibiting factors of the program. Using a descriptive qualitative approach, data were collected through interviews, observations, and documentation, involving the principal, PAI teachers, and students selected through purposive sampling techniques. The findings reveal that PAI teachers play roles as educators, leaders, motivators, facilitators, and supervisors, with their supervisory and leadership roles being the most effective in improving students’ discipline and awareness. Supporting factors include adequate school facilities, teacher motivation, and parental support, while the main obstacle is the low level of student awareness, leading some students to neglect participation in Friday prayers. The Friday prayer program has proven effective in instilling Islamic values such as discipline, responsibility, and a sense of togetherness, while also contributing to the development of students’ positive character. This study highlights the significance of the role of PAI teachers in fostering spiritual character through a comprehensive approach and consistent supervision, offering a model that can be applied in other educational institutions.